PERSPECTIVAS PARA A QUALIDADE DA EDUCAÇÃO BRASILEIRA: UMA ANÁLISE A PARTIR DOS ELEMENTOS CONSERVADORES E TRANSFORMADORES NO PLANO NACIONAL DE EDUCAÇÃO - Diogo, Emilli Moreira (2015)
The research has as main objective to analyze the prospects for quality education as the National Education Plan (Law nº 13.005/2014). This work is characterized as a bibliographical and documentary work, according to a theoretical, and methodological approach guided the historical and dialectical materialism. Beyond, it reflect critically on the proposals and ideas, put forward in documents and literature relevant to the topic investigated which to contribute to the process of analysis and monitoring of the National Education Plan. Then, the survey is exposed in three chapters. At first, we explain them quality meanings and which the most prevalent prospects in concrete reality, a conservative perspective and other transformative. Still, it is observed from the understanding of society as a whole and its contradictions, that the conservative quality of education serves to preserve the capitalist social relations while the manufacturing called perspective. It Is committed to the transformation of capitalist society in an emancipated society. The second chapter is a discussion of the need for a National Education Plan. Also, the State plan must have a commitment to the qualitative improvement of Brazilian education by exposing its historical process and contradictions evident in the legislative process. The third chapter highlights a text analysis approved before the conservative elements and transformers that will guide educational policies over the next decade. From the analysis and discussion of goals and strategies outlined, the National Education Plan it is concluded that there are indications that it leads to a commitment to both the conservative as transformative quality. The findings show the presence of multiple ideologies at the time of drafting and adoption of laws and that the correlation of forces existing in the process materializes the legal and political texts. The planning and the political and educational actions that will guide the forecasts of the National Education Plan (Law nº 13.005/2014) shall show interest in the dispute.